2018
DOI: 10.1002/hyp.13221
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of snow water equivalent datasets over the Saint‐Maurice river basin region of southern Québec

Abstract: A 10‐km gridded snow water equivalent (SWE) dataset is developed over the Saint‐Maurice River basin region in southern Québec from kriging of observed snow survey data for evaluation of SWE products. The gridded SWE dataset covers 1980–2014 and is based on manual gravimetric snow surveys carried out on February 1, March 1, March 15, April 1, and April 15 of each snow season, which captures the annual maximum SWE (SWEM) with a mean interpolation error of ±19%. The dataset is used to evaluate SWEM from a range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…Alternatively, the GlobSnow estimate may have been less than the true mean during melt. This is consistent with previous literature that has found that product estimates that assimilate point depths (such as GlobSnow) typically underestimate depth and SWE due to assimilation of point measurements in exposed areas (such as airports) that ablate more rapidly than the heterogeneous landscape (including forest cover) that the grid cell represents (Brown, Tapsoba, & Derksen, ; Grünewald & Lehning, ; Neumann et al, ). Passive microwave SWE estimates have known error when water content is present in the snow pack (Dietz et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Alternatively, the GlobSnow estimate may have been less than the true mean during melt. This is consistent with previous literature that has found that product estimates that assimilate point depths (such as GlobSnow) typically underestimate depth and SWE due to assimilation of point measurements in exposed areas (such as airports) that ablate more rapidly than the heterogeneous landscape (including forest cover) that the grid cell represents (Brown, Tapsoba, & Derksen, ; Grünewald & Lehning, ; Neumann et al, ). Passive microwave SWE estimates have known error when water content is present in the snow pack (Dietz et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Correlations between GlobSnow and the R4 products are strong across 305 most snow covered regions of the northern hemisphere (GS-R4), with the exception of parts of Arctic Canada and the ephemeral snow zones of both North America and Eurasia (note that alpine areas are masked in the GlobSnow product). As noted earlier, the performance of GlobSnow is closely tied to the density of snow depth data used as inputs to the retrievals (Larue et al, 2017;Brown et al, 2018) which likely contributes to the low correlations in parts of Arctic Canada where there are relatively few snow depth observations. The NASA AMSR-E historical dataset exhibits very weak anomaly correlations with the R4 datasets (Nh-R4), and even negative correlations over the boreal forest of North America and parts of central and eastern Siberia.…”
Section: Correlation Analysis 275mentioning
confidence: 96%
“…The ability of GlobSnow to retain sensitivity to deeper snow than the AMSR-E products is due to the assimilation of daily surface snow depth observations which work to 'nudge' the retrievals to higher values (Pulliainen, 2006). In observation sparse regions such as northern Quebec, the GlobSnow 185 retrieval must rely more on the passive microwave retrievals, which increases uncertainty in these areas (Larue et al, 2017;Brown et al, 2018) compared to forested, deep snow regions with a dense observation network such as Finland (Takala et al, 2011).…”
Section: Climatologymentioning
confidence: 99%
“…The potential formation of clusters of grains, which increases the effective snow grain size, is not taken into account, generating uncertainties (Picard et al, 2013). Several studies have shown that DMRT-ML needed an effective scaling factor to represent the stickiness between snow grains and to correct the snow microstructure representation (Brucker et al, 2011;Roy et al, 2013;Royer et al, 2017). Larue et al (2018) have shown that a mean snow stickiness parameter (τ snow ) of 0.17 was optimal to simulate T Bsnow over boreal snow in Quebec (RMSE of 27 K) when DMRT-ML is driven by Crocus snow profiles.…”
Section: Coupling Of Crocus and Dmrt-mlmentioning
confidence: 99%
“…This contribution does not only depend on the fraction of forest cover, but also on the biomass (liquid water content, LWC), the vegetation volume, and the canopy structure (stem, leaf, trunk) (Franklin, 1987). To adjust snowpack model simulations, several studies suggest using radiative transfer models, coupled to a snowpack model, to take into account the different contributions to the PMW signal at the top of the atmosphere and to directly assimilate PMW satellite observations (Brucker et al, 2011;Durand et al, 2011;Langlois et al, 2012;Roy et al, 2016). However, the assimilation of PMW must be used with care, and a good understanding of the interactions between the properties and microwave emission of the snowpack is crucial to avoid degradation of the SWE estimates.…”
Section: Introductionmentioning
confidence: 99%